Studi Jamur Aspergillus fumigatus di Pasar Cakranegara Kota Mataram Penyebab Penyakit Aspergillosis Menggunakan Media Pertumbuhan Potato Dextrose Agar - Urip Urip; Yunan Jiwintarum; Ni Luh Putu Gita Gandi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
This study aims to isolate, identify, and analyze the fungus Aspergillus fumigatus that causes aspergillosis in Cakranegara Market, Mataram City using Potato Dextrose Agar (PDA) growth media. This research method uses descriptive observation, with Non-Random Purposive Sampling technique. The research sample amounted to 15 consisting of 3 types, namely: air, vegetables, and food (market snacks). Each sample was prepared and then isolated using PDA media and incubated for 3 x 24 hours at 37ºC, then identified and analyzed to find the fungus Aspergillus fumigatus in each of these samples. Based on the research that has been done, the results obtained from 15 samples, namely 9 positive samples (+) found Aspergillus fumigatus and 6 negative samples (-) Aspergillus fumigatus was found. Details of the percentages in each sample, namely: in the air sample, 4 of 5 samples (80%) were positive for Aspergillus fumigatus, in the vegetable sample, 3 out of 5 samples (60%) were positive for Aspergillus fumigatus, and in the food sample, 2 were obtained. of 5 samples (40%) positive found Aspergillus fumigatus. The highest percentage of Aspergillus fumigatus was found in air samples, which is a direct contact that causes aspergillosis. The percentage of the total sample found by Aspergillus fumigatus was 60%.